2022
DOI: 10.1177/0734242x221084077
|View full text |Cite
|
Sign up to set email alerts
|

System dynamics-based prediction of municipal solid waste generation in high-cold and high-altitude area: The case of Lhasa, Tibet

Abstract: The ecological environment in high-cold and high-altitude area is fragile and sensitive, which raise higher claim for municipal solid waste (MSW) management. In the high-cold and high-altitude area, there are problems, such as the mismatch between the actual amount of MSW generated and the scale of transportation and treatment facilities, and the inefficiency of MSW management. In terms of MSW forecasting methods, it is also difficult to forecast due to the lack of data. This study is the first to propose a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Economic growth creates a lot of waste, especially in high-income and upper-middleincome countries [32], which exacerbates environmental problems [33]. Moreover, the ontological insecurities of those in low-income economic brackets indicate that they feel as though they are not in control, which subsequently leads to excessive amounts of waste being produced by such consumers [34]; however, Liu et al found that a synergistic consideration of the GDP growth rate, an urban construction policy, and a tourism development policy can significantly reduce increases in MSW [35]. In developed regions, people are more likely to abide by environmental commitments made by the government and corporations than in poor or developed regions [36].…”
Section: Economic Developmentmentioning
confidence: 99%
“…Economic growth creates a lot of waste, especially in high-income and upper-middleincome countries [32], which exacerbates environmental problems [33]. Moreover, the ontological insecurities of those in low-income economic brackets indicate that they feel as though they are not in control, which subsequently leads to excessive amounts of waste being produced by such consumers [34]; however, Liu et al found that a synergistic consideration of the GDP growth rate, an urban construction policy, and a tourism development policy can significantly reduce increases in MSW [35]. In developed regions, people are more likely to abide by environmental commitments made by the government and corporations than in poor or developed regions [36].…”
Section: Economic Developmentmentioning
confidence: 99%